Modern public administration - Nigro, Felix A.; Nigro , Lloyd G. (Philippines : HarperCollins Publishers, 1989)
In this seventh edition of Modern Public Administration , all the material in the book has been updated. There are two ne chapter. "managing under fiscal stress and "The Future of public administration."
Part One. Administration and policy -- Part Two. Administration and politics -- Part Three. Administrative organization and bureaucracy -- Part Four. Basic problems and management -- Part Five. Personnel administration -- Part Six. Financial administration -- Part Seven. Legislative administration and judicial administration and judicial administration -- Part Eight. Administrative responsibility -- Part Nine. The Future of public administration.
Includes index.
Keywords: PUBLIC ADMINISTRATION